2009
DOI: 10.1016/j.eplepsyres.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The descriptive epidemiology of epilepsy—A review

Abstract: Epilepsy is a chronic disease experienced by millions and a cause of substantial morbidity and mortality. This review summarizes prevalence and incidence studies of epilepsy that provided a clear definition of epilepsy and could be age-adjusted: requirements if comparisons across studies are to be made. Although few exceptions, age-adjusted prevalence estimates from record-based studies (2.7 to 17.6 per 1000), are lower than those from door-to-door surveys (2.2 to 41.0 per 1000). Age-adjusted incidence ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
494
5
30

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 785 publications
(558 citation statements)
references
References 71 publications
29
494
5
30
Order By: Relevance
“…Epilepsy affects approximately 2.8 million Americans, approaching 1% of the general population, 28 disproportionately affecting the elderly, as well as Blacks, especially black men. 29 Despite its high prevalence, the economic burden of epilepsy has been less well studied than that of other neurological diseases.…”
Section: Epilepsymentioning
confidence: 99%
“…Epilepsy affects approximately 2.8 million Americans, approaching 1% of the general population, 28 disproportionately affecting the elderly, as well as Blacks, especially black men. 29 Despite its high prevalence, the economic burden of epilepsy has been less well studied than that of other neurological diseases.…”
Section: Epilepsymentioning
confidence: 99%
“…Recently an excellent descriptive review concerning the epidemiology of epilepsy was published. 11 Several evidences demonstrated that the epileptic seizures alter bloodbrain barrier (BBB) properties and permeability. 31,54,117 Particularly, a recently in vivo study demonstrated the dynamic changes of BBB permeability during epileptogenesis.…”
Section: Epilepsymentioning
confidence: 99%
“…La epilepsia es más común en países en vías de desarrollo (13)(14)(15)(16)(17), con prevalencias estimadas ajustadas a la edad entre 2,7/1000 a 17,6/ 1000 habitantes, y con rangos de incidencia de 16/ 100 000 a 51/ 100 000 habitantes (13). Su mayor incidencia ocurre en los extremos de la vida.…”
Section: Epidemiologíaunclassified
“…Su mayor incidencia ocurre en los extremos de la vida. 13,14 Se han reportado variaciones regionales respecto a la prevalencia de epilepsias, así en el año 2000 se reportó en África la prevalencia de epilepsia de diferentes países con una variación entre el 5.2/1,000 a 58/1,000 habitantes; y una incidencia cruda para todos los tipos de epilepsia de 24.5/100,000, y adicionalmente 13.6/100,000 (56%) con epilepsia de localización sintomática (13,15).…”
Section: Epidemiologíaunclassified